Factors Motivating Graduate Students to Enrol for Post Graduate Studies at the University of Eldoret, Kenya - Sisimwo , Joshua S.; Dimo, H. O.; Kikwai , J. (African Journal of Education,Science and Technology (AJEST), 2025)
In Kenya, potential students have the opportunity to acquire tertiary education through several avenues including; diploma, bachelors‟, masters‟ and doctorate degree programs. Presently, undergraduates comprise the largest number of students at the University of Eldoret, (UoE). Little is known about the factors motivating some students to pursue post graduate studies. This study sought to establish factors that motivate graduates to enroll for postgraduate studies at the UoE. The study analyzed personal, environmental, and institutional factors as determinants of the academic self-efficacy. This study was conducted using ninety four participants at the UoE. Survey research design was used with instruments that measure the extent to which various factors influenced one‟s motivation to enroll for postgraduate studies. The study found that predictable time of course completion, favorable learning conditions and affordability of programs acted as motivators for masters‟ students. Friendly and qualified teaching staff and affordability of the program appeared to be the most important institutional motivating factor for doctoral students. However, the findings reveal that doctoral students expect to gain more respect than master degree students. Master students expect to acquire new jobs and cope with the current work place demands. The study recommends that the UoE should not only consider programs that are geared specifically to income, job, or career enhancement but also programs that offer personal motivation to the students. Additionally, the university should roll out a scholarship program for qualified and deserving students. Lastly, the study recommends that UoE should design programs that meet work place demands.